Peridynamic investigation of surface cracks in optimality criterion-based topology optimization for additive manufacturing (Journal of Additive Manufacturing Technologies, 2023)
Topology optimization (TO) is extensively used for reducing the weight of engineering parts that require higher performance in aerospace, automotive, and defense industries. Additive manufacturing (AM), a practical layer-by-layer material deposition process, is commonly employed to fabricate geometrically complex designs obtained from TO. However, AM processes may result in manufacturing-induced structural discontinuities (surface cracks or voids) that must be considered in the design stage. Nevertheless, most TO algorithms cannot realistically handle these structural cracks/defects since they mainly employ classical continuum-mechanics formulations combined with the finite element method (FEM). On the other hand, peridynamics (PD), a non-local meshless approach, can effectively model any structural discontinuity without the need for an additional effort by breaking non-local interactions. In this study, we combine PD and optimality criterion-based TO methods to investigate the effect of surface cracks on the three-dimensional structural design. For a comparative study, these cracks are also modeled using FEM-TO by eliminating the elements in the cracked region. Optimal geometries and total strain energies obtained from PD are compared with those from FEM for the benchmark case with/without surface cracks. Finally, the advantage of PD is revealed for modeling structural discontinuities in TO.
Keywords: Topology optimization; peridynamics; crack modelling; additive manufacturing; finite element method